The philosophers' quarrel: Rousseau, Hume, and the limits of human understanding - Zaretsky, Robert (Yale University Press, 2009)
The rise and spectacular fall of the friendship between the two great philosophers of the eighteenth century, barely six months after they first met, reverberated on both sides of the Channel. This title explores the unfolding rift between two of the greatest of Enlightenment thinkers, Jean-Jacques Rousseau and David Hume.